Systematic Transcriptome and Regulatory Network Analyses Reveal the Hypoglycemic Mechanism of Dendrobium fimbriatum - Zhang, Qiong (Mol Ther Nucleic Acids, 2019)
Type 2 diabetes (T2D) is a long-term metabolic disorder disease characterized by high blood sugar and relative lack of insulin. Previous studies have demonstrated that Dendrobium has potent glucose-lowing effects and may serve as add-ons or alternatives to classic medications for T2D prevention and treatment, but the underlying molecular mechanisms were still unclear. We performed biochemical and transcriptional profiling (RNA sequencing [RNA-seq] and microRNA sequencing [miRNA-seq]) analyses on the pancreas and liver of Dendrobium fimbriatum extract (DFE)-fed diabetic rats and control animals. Our sequencing and experimental data indicated that DFE significantly alleviated diabetes symptoms through inhibiting inflammation and preventing islet cell apoptosis in diabetic pancreas. Transcription factors in Stat/nuclear factor κB (NF-κB)/Irf families combined with miR-148a/375/9a served as key regulators in the inflammation and apoptosis pathways under DFE administration. Meanwhile, DFE improved the energy metabolism, lipid transport, and oxidoreductase activity in the liver, and thus decreased lipid accumulation and lipotoxicity-induced hepatocyte apoptosis. Our findings revealed that DFE may serve as a potential therapeutic agent to prevent T2D, and also showed the combination of transcriptome profiling and regulatory network analysis could act as an effective approach for investigating potential molecular mechanisms of traditional Chinese medicine on diseases.